Calculating Postnatal Growth Velocity in Very Low Birth Weight (VLBW) Premature Infants - Patel, Aloka L (2009)
OBJECTIVE: Currently, there is no standardized approach to the calculation of growth velocity (GV; g/kg/day) in hospitalized very low birth weight (VLBW) infants. Thus, differing methods are used to estimate GV, resulting in different medical centers and studies reporting growth results that are difficult to compare. The objective of this study was to compare actual GV calculated from infant daily weights during hospitalization in a Neonatal Intensive Care Unit (NICU) with estimated GV using two mathematical models that have previously been shown to provide good estimated GVs in extremely low birth weight infants: an exponential model (EM) and a 2-Point model (2-PM). STUDY DESIGN: Daily weights from 81 infants with birth weights of 1000–1499g were used to calculate actual GV in daily increments from two starting points: (1) birth and (2) day of life of regaining birth weight. These daily GV values were then averaged over the NICU stay to yield overall NICU GV from the two starting points. We compared these actual GV with estimated GV calculated using the EM and 2-PM methods. RESULTS: The mean absolute difference between actual and EM estimates of GV demonstrated <1% error for 100% of infants from both starting points. The mean absolute difference between actual and 2-PM estimates demonstrated <1% error for only 38% and 44% of infants from birth and regaining birth weight, respectively. The EM was unaffected by decreasing BW and increasing length of NICU stay, while the accuracy of the 2-PM was diminished significantly (p<.001) by both factors. CONCLUSIONS: In contrast to the 2-PM, the EM provides an extremely accurate estimate of growth velocity in larger VLBW infants, and its accuracy is unaffected by common infant factors. The EM has now been validated for use in all VLBW infants to assess growth and provides a simple-to-use and consistent approach.